Interesting limit!

maxhk

New member
Joined
Sep 26, 2011
Messages
26
Hello,

I have the following question :

If \(\displaystyle x = x(t)\) and \(\displaystyle y = y(t)\) satisfy the equation :

\(\displaystyle (x^c * e^{-dx}) (y^a *e^{-by}) = k\),

where \(\displaystyle k, a, b, c, d \) are positive constants.

Show that neither \(\displaystyle x(t) \) nor \(\displaystyle y(t) \) can \(\displaystyle \to \infty\) as \(\displaystyle t \to \infty \).
 
Last edited:
a=b=c=d=k=1 gives quite a bit of insight.

Still more insight from the logartihm.

\(\displaystyle c\cdot log(x) + a\cdot log(y) = log(k) + dx + by\)
 
Last edited:
Top